Patients' Perceptions of Nurses' Behaviour That Influence Patient Participation in Nursing Care: A Critical Incident Study - Inga E. Larsson; Monika J. M. Sahlsten; Kerstin Segesten; Kaety A. E. Plos (Nursing Research and Practice)
Patient participation is an important basis for nursing care and medical treatment and is a legal right in many Western countries. Studies have established that patients consider participation to be both obvious and important, but there are also findings showing the opposite and patients often prefer a passive recipient role. Knowledge of what may influence patients' participation is thus of great importance. The aim was to identify incidents and nurses' behaviours that influence patients' participation in nursing care based on patients' experiences from inpatient somatic care. The Critical Incident Technique (CIT) was employed. Interviews were performed with patients (𝑛=17), recruited from somatic inpatient care at an internal medical clinic in West Sweden. This study provided a picture of incidents, nurses' behaviours that stimulate or inhibit patients' participation, and patient reactions on nurses' behaviours. Incidents took place during medical ward round, nursing ward round, information session, nursing documentation, drug administration, and meal.